HPLC method for identification and quantification of benzimidazole derivatives in antiparasitic drugs - Kulik, Anna; Białecka, Wanda; Podolska, Marzena; Kwiatkowska-Puchniarz, Barbara; Mazurek, Aleksander (Acta Poloniae pharmaceutica, 2011)
The subject of the study was to develop a versatile HPLC system for identification and determination of four benzimidazole derivatives in the antiparasitic drugs. The tests covered: Zentel, Panacur, Vermox tablets and Systamex suspension. A satisfactory separation was obtained using the Nucleosil C8 column in the gradient system composed of mobile phase A: 85% orthophosphoric acid / water / acetonitrile in 0.05:75:25, v/v/v ratio, and mobile phase B: 85% orthophosphoric acid / water / acetonitrile in 0.05:50:50, v/v/v ratio. Both phases were adjusted to pH = 4.5 with 15% sodium hydroxide solution. A detection at 288 nm for oxfendazole and 254 nm for albendazole, fenbendazole and mebendazole was applied. The correlation coefficients in the range 0,9997 - 0,9999 proved that the calibration curves were linear. The method was validated in terms of selectivity, accuracy and precision.